2018
DOI: 10.1071/an16240
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of docility score of Australian Angus and Limousin cattle

Abstract: The temperament of cattle is believed to affect the profitability of the herd through impacting production costs, meat quality, reproduction, maternal behaviour and the welfare of the animals and their handlers. As part of the national beef cattle genetic evaluation in Australia by BREEDPLAN, 50 935 Angus and 50 930 Limousin calves were scored by seedstock producers for temperament using docility score. Docility score is a subjective score of the animal’s response to being restrained and isolated within a crus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
6
0
2
Order By: Relevance
“…There is also a notable variation in estimated heritability observed between different breeds of beef cows [ 37 ]. This is supported by the differences between differences reported by other studies, with heritability of docility varying between Angus and Limousin [ 49 ] and Pirenaica [ 41 ] cattle. This variation can be attributed to innate breed differences and variation in measures and calculation of temperament and /or docility.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…There is also a notable variation in estimated heritability observed between different breeds of beef cows [ 37 ]. This is supported by the differences between differences reported by other studies, with heritability of docility varying between Angus and Limousin [ 49 ] and Pirenaica [ 41 ] cattle. This variation can be attributed to innate breed differences and variation in measures and calculation of temperament and /or docility.…”
Section: Resultssupporting
confidence: 71%
“…The subjective nature of not only the measurement but of the nomenclature of assessing behavioural traits is demonstrated by a study which reports the temperament of cattle [ 37 ] citing a method used to report docility [ 46 ]. Docility was generally given a subjective score [ 41 , 47 , 48 , 49 ], however, this could be further modelled to include maternal and environmental effects [ 48 ]. Modelling multiple traits to calculate docility was a technique used by Phocas et al, 2006 who reported docility as a linear combination of aggression and escape attempts from an enclosed area [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cattle received similar treatments on entry to the feedlot as per Experiment 1. Cattle docility scores [ 17 , 48 ] were assessed in 1 to 5 categories based on cattle temperament and behaviour when entering and exiting the crush with a score of 1 being assigned to cattle that were calm and quiet in the crush and on exit, and 5 for cattle that were highly agitated and nervous.…”
Section: Methodsmentioning
confidence: 99%
“…According to (Riley et al 2016;Costilla et al 2020) the heredity of the temperament is moderate within h 2 = 0.30-0.35. In the opinion of Walkom et al (2016), the heredity parameter for the Aberdeen Angus cattle breed is 0.21. er caregivers. Furthermore, they require to care for a shorter period, and the necessary safety and humane treatment are ensured.…”
Section: Resultsmentioning
confidence: 99%